Isolation of oleosin and determination of oil body size in Brassica juncea - Ibandalin Mawlong; MS Sujith Kumar; PD Meena; Devesh Pathak (Journal of Oilseed Brassica, 2026)
Oil bodies are structural entities that store triacylglycerols (TAG) in oilseeds. Each oil body contains a matrix oftriacylglycerol (TAG) surrounded by a layer of phospholipids and its associated oil body proteins. Description of oilbody and its associated proteins has not been well documented in Brassica juncea unlike Arabidopsis which is a relatedspecies. In this study extraction of oil bodies (OB) was done by flotation method following which the presence andintegrity of oil bodies was confirmed using compound light microscope. The size of OB ranged from 0.58 (Maya) to 1.05μm (HB9902). The major phospholipid as profiled by TLC was phospotidylcholine. Purification of structural proteinswas done by altering the time of urea (8M) treatment. The proteins isolated from the oil bodies showed multiple bandsin SDS-PAGE that included oleosin protein. Downstream purification of oil body proteins was standardized to removefurther unspecific bands by additional urea treatment with time of incubation 30 min, 1h and overnight at roomtemperature.Out of the three, overnight incubation showed less appearance of unspecific bands. A comparative studyamong selected genotypes was also done showing oil content to be inversely related to oil body size and positivelycorrelated to oleosin content. Hence by manipulating the oleosin proteins, it may be possible to increase the oil content.